Surrogate and clinical outcomes following ischemic postconditioning during primary percutaneous coronary intervention of ST‐Segment elevation myocardial infarction: A meta‐analysis of 15 randomized trials. Issue 6 (14th July 2014) - Khalili, Houman; Patel, Vishal G.; Mayo, Helen G.; de Lemos, James A.; Brilakis, Emmanouil S.; Banerjee, Subhash; Bavry, Anthony A.; Bhatt, Deepak L.; Kumbhani, Dharam J.
<x xml:space="preserve">Abstract</x> Objectives To conduct a meta‐analysis on surrogate and clinical outcomes with myocardial ischemic postconditioning (IPoC) following revascularization with primary percutaneous intervention (PPCI) for ST‐segment myocardial infarction (STEMI) compared with PPCI alone. Background Reperfusion injury remains an important problem following PPCI for STEMI. Trials of IPoC have mainly focused on cardiac biomarkers; the impact on clinical outcomes is unknown. Methods Clinical trials that randomized STEMI patients to IPoC as compared with conventional PPCI were included for analysis. Results A total of 15 randomized trials with 1, 545 patients met our selection criteria (785 underwent IPoC + PPCI, 760 PPCI alone). Mean follow‐up for clinical outcomes was 4.7 months. The mean ischemic time was 225 min. ST‐segment resolution (Relative Risk [RR] = 0.98; 95% Confidence Intervals [CI] 0.85–1.13; P = 0.75) and infarct size (Weighted mean difference [WMD] = −2.53%, 95% CI −6.10 to 1.05; P = 0.17) were similar between the IPoC + PPCI vs. PPCI arms. Left ventricular ejection fraction at follow‐up was marginally higher in the IPoC (WMD = 4.15%, 95% CI 0.19–8.12%, P = 0.04). No differences were noted in any of the clinical outcomes studied, including mortality (RR = 1.52; 95% CI 0.77–2.99; P = 0.23), recurrent MI (RR = 3.04; 95% CI 0.74–12.54; P = 0.12); stent thrombosis (RR = 1.24, 95% CI 0.51–3.04; P = 0.83) or the composite MACE outcome (RR = 1.53; 95% CI 0.89–2.63; P = 0.13). Conclusions: IPoC following PPCI is not associated with improvements in surrogate or clinical outcomes at 5 months as compared with PPCI alone. Our findings indicate no role for IPoC in the routine management of patients with STEMI. © 2014 Wiley Periodicals, Inc.